EVALUATION OF THE INSECTICIDAL, LARVICIDAL AND OVICIDAL EFFECTS ON CALLOSOBRUCHUS MACULATUS OF ESSENTIAL OILS OF CYMBOPOGONGIGANTEUS AND OF XYLOPIA AETHIOPICA - NOUDOGBESSI, JEAN PIERRE AKODOGBO; KEKE, Martin; AVLESSI, FÉLICIEN; DANGOU SOSSOU, JUSTINE; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2009)
The chemical composition of essential oils extracted from leaves of Cymbopogon giganteus (Hochst.) Chiov and fruits of Xylopia aethiopica (Dunal) A. Richard has been studied by gas chromatography (GC) and gas chromatography coupled with mass spectrometry (GC/MS). The doses of each of these essential oils tested on Callosobruchus maculatus at temperatures between 22 °C and 31 °C and a relative humidity of 80% are 0, 10, 20, 30 and 40μL.mL-1. The tests of conservation carried out of cowpea seeds (Vigna unguiculata L Walp.) of local variety "Chawé" showed that these essential oils have variously exhibited larvicidal and ovicidal effects on larvae and eggs of C. maculatus (Fabricius) adult to the highest dose tested (40 μL.mL-1).The damage generated by C. maculatus and its larvae were evaluated by the percentages of attack (A) and the loss in weight of seeds of cowpea (B).
Keywords: essential oil; Cymbopogon giganteus; Xylopia aethiopica; cowpea; "Chawe" Callosobruchus maculatus; weight loss